A cloned DNA segment from the telomeric region of human chromosome 4p is not detectably rearranged in Huntington disease patients. - Pritchard, C (1990)
Genetic linkage studies have mapped the Huntington disease (HD) mutation to the distal region of the short arm of human chromosome 4. Analysis of recombination events in this region has produced contradictory locations for HD. One possible location is in the region distal to the D4S90 marker, which is located within 300 kilobases of the telomere. Other crossover events predict a more centromeric position for HD. Here we analyze the telomeric region of 4p in detail. Cloned DNA segments were derived from this region by utilizing a radiation-induced somatic cell hybrid as a source of DNA combined with preparative pulsed-field gel electrophoresis to enrich for the telomeric fraction. Additional DNA was obtained by using the cloned segments as multiple start points for cosmid walks. This strategy proved to be an effective method for cloning 250 kilobases of DNA in the region telomeric to D4S90. Hybridization analysis with the cloned DNA did not provide any evidence for the presence of rearrangements of 100 base pairs or greater in the DNA of individuals affected with HD. We also found no change in the size or structure of the 4p telomere in these samples.